Field and Laboratory Studies on Four Species of Sea Squirts and their Larvae (Global Journal of Science Frontier Research, 2016)
The aim of this study was to characterize adult distribution with respect to light and analyze ovary contents in the four seasons of the year. The swimming behavior of Ciona intestinalis, Molgula manhattensis, Ascidella aspersa and Phallusia mammilata larvae against certain abiotic factors were commented. For the field data on adult distributions, one-way analysis of variance (ANOVA) was applied to test for differences in adult orientation, with surface orientation as a fixed factor. Two adult species (Ciona intestinalis and Molgula manhattensis) showed no orientation with respect to light while in the other two species (Ascidella aspersa and Phallusia mammilata) light exerted a significant effects on the orientation and density of individuals. To evaluate among the different species the level of gregariousness found in the field, the number of individuals per clump for each species has been compared using one-way ANOVA, with species as a fixed factor. Artificial heterologous inseminations were carried out.
Keywords: field data - gregariousness - heterologous inseminations -adult orientation - larval settlement 2013; phototaxis - geotaxis